Macromolecular Metal Carboxylates and Their Nanocomposites - Pomogailo, A. D. (Springer Series in Materials Science,, 2010)
Data on the synthesis and physicochemical studies of salts of mono- or dibasic unsaturated carboxylic acids and macromolecular metal carboxylates are generalised and described systematically. The structures and properties of the COO group in various compounds and characteristic features of the structures of carboxylate are analysed. The main routes and kinetics of polymerisation transformations of unsaturated metal carboxylates are considered. The attention is focused on the effect of the metal ion on the monomer reactivity and the polymer morphology and structure. The possibility of stereochemical control of radical polymerisation of unsaturated metal carboxylates is demonstrated. The electronic, magnetic, optical, absorption and thermal properties of metal (co)polymers and nanocomposites and their main applications are considered.